Improving the evacuation preparedness planning for disaster relief in Kelantan by using geographical information system [electronic resource] - Muhammad Wafiy Adli Ramli, author 635299; Shazwin Mat Taib, supervisor 513808; Nor Eliza Alias, 1984-, supervisor 184883; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Pengurusan Alam Sekitar)) - Universiti Teknologi Malaysia, 2016